2008
DOI: 10.1002/bem.20425
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high strength static magnetic fields and ionizing radiation on gene expression and DNA damage in Caenorhabditis elegans

Abstract: Magnetic resonance imaging with high static magnetic fields (SMFs) has become widely used for medical imaging purposes because SMFs cause fewer genotoxic side effects than ionizing radiation (IR). However, the effect of exposure to high SMFs on global transcription is little understood. We demonstrate that genes involved in motor activity, actin binding, cell adhesion, and cuticles are transiently and specifically induced following exposure to 3 or 5 T SMF in the experimental model metazoan Caenorhabditis eleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…The data in literature, together with our observations, support the idea that the application of magnetic fields could effectively stimulate endothelial cells through a transient alteration of the expression of certain genes, suggesting the safety of SMFs as described in other model organisms such as C. elegans [Kimura et al, 2008].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The data in literature, together with our observations, support the idea that the application of magnetic fields could effectively stimulate endothelial cells through a transient alteration of the expression of certain genes, suggesting the safety of SMFs as described in other model organisms such as C. elegans [Kimura et al, 2008].…”
Section: Discussionsupporting
confidence: 85%
“…The reorganization and breakdown of different cytoskeleton elements appears to be related to a modified Ca 2þ homeostasis or altered phosphorylation/dephosphorylation mechanisms. Hence, the putative target molecules of SMFs seem to be genes encoding Ca 2þ -binding and actin-binding proteins related to locomotive behavior, cytoskeleton components, and cell adhesion molecules, which has also been observed in C. elegans where these genes are transcriptionally controlled in response to high magnetic fields [Kimura et al, 2008]. Moreover, the exposure to MFs can determine modifications not only in the cell shape but also in the structure of the cell plasma membrane [Rosen, 1993;Chionna et al, 2003Chionna et al, , 2005, which involves changes in transmembrane potential and the activity of Ca 2þ channels [Panagopoulos et al, 2000].…”
Section: Discussionmentioning
confidence: 88%
“…However, there was no difference in MN frequency between SMF-exposed and unexposed samples when we checked the effect of SMF in itself by switching off the MRI pulse sequences. Based on a few in vitro and in vivo studies, it was reported that a combination of SMF exposure with chemicals or radiation was shown to induce DNA single-strand breaks, MN formation, and CA, although exposure to a SMF alone did not affect DNA damage [Nakahara et al, 2002;Miyakoshi, 2005;Suzuki et al, 2006;Kimura et al, 2008;Kubinyi et al, 2010]. In this study, we cannot exclude that the SMF component of the MRI was responsible for the enhanced effects on DNA and chromosomal damage.…”
Section: Discussionmentioning
confidence: 69%
“…In C. elegans, a short-term treatment with SMFs induced fluctuations in (Miyakawa et al, 2001;Kimura et al, 2008). The current study is based on the hypothesis that, given sufficient intensity, SMFs can shorten the life cycle and cause premature aging in nematodes.…”
Section: Introductionmentioning
confidence: 99%